Providing a forum for European criminology: connecting scholars with different perspectives and shared goals - Treiber, Kyle (European journal of criminology, 2025)
In this contribution, we reﬂect on the understanding we have gathered of European criminology during our ﬁve years as current Editor-in-Chief and Managing Editor of the European Journal of Criminology. Applying an analytic approach, we reﬂect on the deﬁning features of European criminology, the boundaries of European criminology, and the goalsof European criminology. We afﬁrm that European criminology’s most deﬁning feature is its shared differences and scholarly goals to be theoretically guided, methodologically inclusive, empirically cross-comparative, and policy oriented. We conclude that the European Journal of Criminology provides an important space in which these differences and goals can be celebrated and shared.